Changes
From Karnataka Open Educational Resources
783 bytes added
, 17:04, 12 August 2014
Line 164: |
Line 164: |
| #In this problem we prove that 'c' will be the harmonic mean between 'a' and 'b' | | #In this problem we prove that 'c' will be the harmonic mean between 'a' and 'b' |
| #That is we just show that c = <math>\frac{2ab} {a + b}</math> | | #That is we just show that c = <math>\frac{2ab} {a + b}</math> |
| + | ==Solution of the problem== |
| + | Assumption :- |
| + | #He know the formula for A.M , G.M and H.M |
| + | #He know the basic operation. |
| + | #He know substitute the values |
| + | ==Algorithm== |
| + | The formula for arithmetic mean between 'a' and 'b' is A.M = <math>\frac{a + b} {2}</math><br> |
| + | The formula for geometric mean between 'a' and 'b' is G.M = <math>\sqrt{ab}</math><br> |
| + | Then formula for harmonic mean between 'a' and 'c' is H.M = <math>\frac{2ab} {a + b}</math><br> |
| + | Let 'a' be the arithmetic mean of 'b' and 'c'<br> |
| + | That is a = <math>\frac{a + b} {2}</math><br> |
| + | Re-arrange the formula,<br> |
| + | 2 = <math>\frac{b + c} {a}</math> --------->1<br> |
| + | Multiply both side by 'ab' we get,<br> |
| + | 2ab = <math>\frac{ab(b + c)} {a}<br> |
| + | |
| + | Also 'b' is the geometric mean between 'a' and 'c'<br> |
| + | That is b = <math>\sqrt{ac}</math><br> |